Some Novel Phases in Binary System of PbO-Sb2O3 - Guzin Aslan, H. (Asian Journal of Chemistry, 2014)
In this study, we have investigated the PbO-Sb2O3 binary system. PbO and Sb2O3 are reacted using different stoichiometric ratios at 650 °C in an air using a gold and a platinum reaction vessel by heating for 24 h. PbSb2O6, Pb9Sb8O21, Pb4Sb2O8, Pb9Sb8O17, Pb6Sb2O11, Pb5Sb2O9, Pb7Sb2O11, Pb8Sb2O12, Pb9Sb2O13, phases are synthesized and these phases 0.5, 0.692, 0.8, 0.818, 0.857, 0.87, 0.875, 0.88, 0.9 mole fractions, respectively. Reaction products are characterized by the X-ray powder diffraction and by DTA/TG analysis methods.